Analisis Pengaruh Media Sosial Terhadap Prestasi Belajar Siswa - Putri Hamimah; Yuli Astutik; Rusandi Rusandi (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
The continuous development of technology, particularly the significant advancements in the internet, has greatly facilitated human life in various aspects, including education. Social media stands out as a concrete example of the progress in information technology. Videos, blogs, websites, and images on online platforms are utilized by users and followers to create various types of content (Cahyono, 2016). Social media can have a significant impact on educational outcomes, particularly students' academic achievements. The influence exerted by social media can be both positive and negative. Positive effects of social media on academic performance include ease of learning processes, improved interaction skills with others, expanded knowledge, and the use of social media as a tool for personal development. On the other hand, negative impacts of social media on learning outcomes encompass the potential for addiction, exposure to explicit content, a tendency to become lazy in studying, and disruptions in concentration during the learning process. Therefore, it ultimately depends on the individual students' goals; if social media is used positively, it can have beneficial effects on their academic achievements